Reducing the cost for non-blocking in atomic commitment - Guerraoui, R.; Larrea, M.; Schiper, A. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
Non-blocking atomic commitment protocols enable a decision (commit or abort) to be reached at every correct participant, despite the failure of others. The cost for non-blocking implies however (1) a high number of messages and communication steps required to reach commit, and (2) a complicated termination protocol needed in the case of failure suspicions. In this paper, we present a non-blocking protocol, called MDSPC (Modular and Decentralized Three Phase Commit), which enables to trade resiliency against efficiency. As conveyed by our performance measures, MDSPC is faster than existing non-blocking protocols, and in the case of a broadcast network and a reasonable resiliency rate (e.g. 2 or 3) is almost as efficient as the classical (blocking) 2PC. The termination protocol of MDSPC is encapsulated inside a majority consensus protocol. This modularity leads to a simple structure of MDSPC and enables a precise characterization of its liveness in an asynchronous system with an unreliable failure detector.